A heuristic to solve the dynamic lot sizing problem with supplier selection and quantity discounts. (July 2015) - Mazdeh, Mohammad Mahdavi; Emadikhiav, Mohsen; Parsa, Iman
Highlights: We address the single-item dynamic lot sizing problem with supplier selection. The problem is broken down into two different cases (with and without discounts). The model formulation of the problem is given for the case of mixed discount policy. A new heuristic is developed to solve the problem. This method provides averagely high accuracy solutions within low computational time. Abstract: In the present study, the single-item dynamic lot sizing problem with supplier selection is investigated. The problem is broken down into two different cases. In the first case, quantity discounts are not taken into account; in the second case, incremental and all-unit quantity discounts are considered. Due to the complexity of the problems, a new heuristic is developed, which is based on the Fordyce–Webster Algorithm (Fordyce and Webster, 1984). In order to solve the problem where multiple suppliers are considered, a third dimension is added to the matrices used in the Fordyce–Webster Algorithm. The solutions gained using the proposed algorithm are similar to those of Parsa, Khiav, Mazdeh, and Mehrani (2013) in terms of accuracy and computational time. However, the implementation of matrices makes this method easy to explain in comparison with other heuristics developed for similar problems.